Promoting energy audits: Results from an experiment - Philipp-Bastian Brutscher; Pauline Ravillard (European Investment Bank (EIB), 2019)
Energy audits are key to increase investments in energy efficiency, as they allow to overcome the 'information gap'- one of the biggest obstacles to this type of investment. However, on average only 30% of SMEs said to have carried out an energy audit between 2015 and 2018. This paper assesses the effectiveness of policy interventions in promoting energy audits by relying on evidence from a unique online experiment, as part of the European Investment Bank's annual Investment Survey. 1,178 EU firms were asked about their willingness to invest in an energy audit, given different scenarios of randomly drawn policy interventions. These are a level of support, whether it comes in the form of a grant or a tax credit, and whether the audit is conditional on investing in an energy efficiency project after. Findings allow us to quantify by how much the probability that firms invest in energy audits increases, as the combinations of policy interventions vary.
Keywords: 330